Adult Recreational Demands and Barriers - Tayfun Kara, Mehmet Mustafa Yorumazlar, (Pakistan Journal of Medical & Health Sciences, 2022)
Aim: Increasing recreational demands primarily depends on eliminating the factors that prevent people from participating in recreational activities . recreation demand depends on the planning of recreational activities by the administration and the development of recreational areas , starting from the choice of recreational activities on line with the leisure time demands of individuals . The main purpose of this study is to determine the recreational demands of middle-aged and older individuals residing in Kahramanmaras, the factors that prevent their participation in recreational activities and the factors that should be considered during the development of recreation areas in Kahramanmaraş and the construction of new recreation areas. Methods: In the research within the scope of the study , the leisure time barriers scale was applied in the recreation areas in Kahramanmaraş and the data collected from 600 volunteer participants were analyzed using the SPSS 21 program. Results: According to to the results of the research, it was determined that the first of the leisure time inhibitors that prevent the recreational demands of the upper middle individuals is the Lack of Knowledge sub-dimension. The sub-dimension of lack of information is followed by the psychology of the individual, lack of interest, lack of facilities, time and friends sub-dimensions, respectively. Conclusion: Across the scale of leisure barriers , it was determined that the leisure time barriers perceptions of the participants did not differ statistically significantly according to to their gender , marital status and income groups . It is seen that the perceptions of leisure time barriers of individuals over middle age differ statistically significantly according to the age groups, level of education and working status. It is seen that the factor affecting the “ facility sub-dimension ” of the leisure time barriers scale the most is the suitability of the facilities for their age group and the perceptions of the recreational participants , the upper middle class participants .